Viscous Dissipation and Dufour Effects on MHD Free Convection Flow Through an Oscillatory Inclined Porous Plate with Hall and Ion-Slip Current - V. B. Raja kumar, K.; S. Balamurugan, K.; V. Ramana Murthy, Ch.; Ranganath, N. (International Journal of Engineering and Technology, 2018)
In this paper the viscous dissipation and Dufour effects on Unsteady MHD free convective flow through a semi-infinite Oscillatory porous inclined plate of time dependent permeability with Chemical reaction and Hall and Ion-Slip Current in a Rotating System was investigated. The dimensionless governing equations for this investigation are solved analytically by using multiple regular perturbation law. The effects of different parameters on velocity, temperature and concentration fields are shown graphically. Â Â